Bilabial Articulation Pronunciation “B” (L1) and Syafatain Letters “Ba” (L2): Analysis of the pronunciation of the letter Ba in Surah Al-Fatihah - Hikmah Maulani; Muhammad Dhiya Alwan (ALSUNIYAT: Jurnal Penelitian Bahasa, Sastra, dan Budaya Arab, 2023)
This study aims to elaborate on the findings of the utterances of the bilabial letters B and Syafatain huruf Ba spoken by Indonesians as non-Arabic speakers in the context of differences in pronunciation between Arabic and Indonesian letters. The method used in this research is a qualitative approach using participant speakers. Three Indonesian participants recited Surah Al-Fatihah in the mosque environment. Data collection techniques are listening techniques using audio, observation, and interviews. Data analysis used is data reduction with raw data in the form of audio recordings and using a Praat Analysis Computer. This study obtained data on the characteristics and factors that influence the speech articulation of letters B and Ba spoken by Indonesians as non-Arabic speakers. Furthermore, this research has practical implications for the treasures of Arabic-Indonesian phonetic knowledge, also empirically as material for field-based learning studies.